2005
DOI: 10.1007/s10620-005-2728-0
|View full text |Cite
|
Sign up to set email alerts
|

Portal Venous Flow Pattern as a Useful Tool for Predicting Esophageal Varix Bleeding in Cirrhotic Patients

Abstract: This study aimed to evaluate whether (1) the portal venous flow pattern determined by color Doppler sonography could be related to the clinical severity of liver cirrhosis and (2) whether the flow patterns differ between patients with bleeding and nonbleeding esophageal varices. One hundred twenty-nine cirrhotic patients and 60 noncirrhotic healthy controls were enrolled after endoscopic survey for the presence of esophageal varices. Each patient received color Doppler echography to define the pattern of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although some collaterals, including the coronary vein, were too small to be directly viewed at 4D flow MRI, the decrease of flow in the PV because of hepatofugal shunting of blood was sufficient to help detect abnormal flow to the varices. Previous studies showed that flow measurement by using US in the PV (29,30) or in the hepatic veins (31) can be used to predict the presence of varices. Although US-based flow measurement is simpler and less expensive than MRI, it is challenging to measure the flow in the hepatic vasculature at US because of the complexity of anatomy and limited field of view.…”
Section: Quantitative Analysis Of 4d Flow Mrimentioning
confidence: 99%
“…Although some collaterals, including the coronary vein, were too small to be directly viewed at 4D flow MRI, the decrease of flow in the PV because of hepatofugal shunting of blood was sufficient to help detect abnormal flow to the varices. Previous studies showed that flow measurement by using US in the PV (29,30) or in the hepatic veins (31) can be used to predict the presence of varices. Although US-based flow measurement is simpler and less expensive than MRI, it is challenging to measure the flow in the hepatic vasculature at US because of the complexity of anatomy and limited field of view.…”
Section: Quantitative Analysis Of 4d Flow Mrimentioning
confidence: 99%
“…Investigators have attempted to identify characteristics that noninvasively predict the presence of varices. These studies have shown that biochemical, clinical, and ultrasonographic parameters alone or together have good predictive power for noninvasively assessing the presence of EV [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Overall, the most common result of these studies was that parameters such as splenomegaly, thrombocytopenia, Childs score, ascites, portal flow patterns, and platelet count-splenic size ratio were predictors of the presence of EV.…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7][8][9] Not infrequently, this is associated with PV thrombosis. [10][11][12] However, large portosystemic shunts such as SSRSs may jeopardize the portal flow and lead to graft dysfunction due to portal hypoperfusion. 13 The optimal surgical approach to SSRSs has not been well defined.…”
mentioning
confidence: 99%